DEVELOPING A SUSTAINABLE FUTURE BY IDENTIFYING AND UNDERSTANDING THE LIMITATIONS OF THE PAST. A REVIEW OF “DEBUNKING ECONOMICS: THE NAKED EMPEROR OF THE SOCIAL SCIENCES” BY STEVE KEEN - Vasile, Adrian; Costea, Carmen Eugenia (Annals of Spiru Haret University. Economic Series, 2013)
One of the first arguments presented in the start of the book and extensively discussed latter on, is the impossibility of providing a generalization of human behaviour. The pattern of behaviour is central in the economic theory, as all phenomena are illustrated and modelled using this starting point. While actions and preferences can be rigorously modelled at microeconomic level, in most situations, when depicting the society as a whole, further conditions or hypothesis are required. The author sheds light on the improbable or even unrealistic character of such hypothesis, that fail to hold true when confronted with the real world market. From the notion of utility, initially laid down by Bentham, to the development of indifference curves and aggregate consumption patterns, expanding the theoretical work from an individual scope to a wider, community level, requires the adoption of less than logical assumptions such as that all participants have the same preferences and, if obtaining an increase in revenues, they would continue to express the same needs and expectations.